Aplikasi Trip Planner Wisata Jawa Timur Menggunakan Metode Content Based dan Collaborative Based pada Android - Fransisco Edo; Andreas Handojo; Henry Novianus Palit (Jurnal Infra, 2016)
Tourism is an activity which is done by one or many persons for having holiday or recreation. Finding a good tourism spot, which fits with one’s interest and spare time, is not an easy task. In general, tourism information that appears on the websites or in the mobile applications is not based on user's interest. Lack of information is a hassle for someone who is having holiday.Therefore, a recommendation-system application was made using content-based and collaborative-based methods as a means to choose tourism spots in accordance with user's preferences This Android application has features to list tourist spots which suit the user's preferences give some alternate routes to user, show details of the tourism spots, and show their locations in the map.From the conducted test, the system can recommends tourism spotsthat match with user’s preferences, and user can see the recommended alternate routes and the detailed information of the tourist spots.